Sporadic Creutzfeldt-Jakob Disease in a Young Girl With Unusually Long Survival. Issue 4 (11th March 2019) - D'Arcy, Colleen E; Bitnun, Ari; Coulthart, Michael B; D'Amour, Rolande; Friedman, Jeremy; Knox, J David; Rapoport, Adam; Carter, Snead; Widjaja, Elysa; Hazrati, Lili-Naz; Jansen, Gerard H
Abstract: Creutzfeldt-Jakob disease (CJD) is a rapidly progressive, fatal degenerative encephalopathy caused by a pathologically altered form of the prion protein (PrP). CJD is rare, with 1 and 2 cases per million per year reported in the general population, mostly in individuals over 50 years of age. It is almost unknown in the pediatric population. Sporadic CJD with unusually long survival (sCJD-LS), an unusual clinicopathological variant of CJD, has been described mostly in Japanese patients. We present here the first case report of pediatric CJD-LS occurring sporadically in a teenage girl of European descent, with initially rapid neurocognitive decline followed by a prolonged (∼10 years) clinical course. Neuropathological findings at autopsy included generalized cerebral and cerebellar atrophy with relative sparing of the hippocampi, cerebral and cerebellar white and gray matter involvement, minimal spongiform change, PrP deposits in the neocortex, striatum and cerebellum by immunohistochemistry, and protease-resistant PrP by Western immunoblot. With its longer disease duration and atypical manifestations of white matter loss, CJD-LS can be clinically mistaken for other neurodegenerative diseases, or in the pediatric setting for metabolic/genetic conditions. This case clearly demonstrates that with rapid-onset encephalopathy, prion disease should be carefully considered, even in younger patients with slower disease progression.